Stakeholder views on transport corridors and intermodal transport solutions - Hansen, Leif Gjesing (Proceedings from the Annual Transport Conference at Aalborg University, 2007)
This paper presents empirical findings and results from a study conducted as a part of an INTERREG IIIB project on intermodal transport solutions and corridors in the North Sea Region (SUTRANET – Sustainable Transport Research & Development Network in the North Sea Region, www.sutranet.org). The aim of the study has been to explore possibilities and barriers for the development of intermodal transport solutions in selected corridors in the North Sea Region. The North Sea Region is one among several regions appointed by the EU-Commission to exemplify the operationalisation of the concept Motorways of the Sea (European Commission, 2004). The policies of promoting Motorways of the Sea is aiming at revitalise the short-sea-shipping within Europe as a transport industry, but also to relieve the heavily congested road network in central regions (European Commission, 2001). However, the success of Motorways of the Sea relies not only on the implementation of shipping lines between specific ports, but also the hinterland connections of these ports and the logistical decision- making among co-ordinators of transport flows (European Commission, 2003). The traditional role of forwarding firms as freight integrators is being challenged by other actors within the transport system, e.g. ferry and shipping lines, ports and train operators. The rationale for this development has been the increased focus by the transport sectors stakeholders on the control of guiding transport flows through specific transport networks of own interest. Most transport firms are mobile in their activities by nature, but are in reality confined in their day-to-day operations to different forms of relative fixed network structure – e.g. railway lines, ferry routes and ports, cost- efficient choice of road routes, etc. This represents potentials and barriers for promotion of intermodal transport solutions, since it points to the importance of governance of transport networks by different transport stakeholders as “gate-keepers” for what kind of transport modes and routes are selected. In this study stakeholders from Danish and Norwegian ports, ferry operators, train operators, forwarding and road haulage firms has been interviewed in order to analyse how logistical decision- making affect the organisational and physical configuration of intermodal transport solutions in the transport corridor between Scandinavia and the European Continent.